Climate change, natural disasters, and migration - Linguère Mously Mbaye (IZA World of Labor, 2017)
The relationship between climatic shocks, natural disasters, and migration has received increasing attention in recent years and is quite controversial. One view suggests that climate change and its associated natural disasters increase migration. An alternative view suggests that climate change may only have marginal effects on migration. Knowing whether climate change and natural disasters lead to more migration is crucial to better understand the different channels of transmission between climatic shocks and migration and to formulate evidence-based policy recommendations for the efficient management of the consequences of disasters.
Keywords: J61; O12; O13; O15; Q5; 330; climate change; natural disasters; migration; remittances; mitigation strategy